Very Long-Term Follow-Up in Cardiac Resynchronization Therapy: Wider Paced QRS Equals Worse Prognosis - Patrick Leitz (MDPI AG, 2021)
Background: Different electrocardiogram (ECG) findings are known to be independent predictors of clinical response to cardiac resynchronization therapy (CRT). It remains unknown how these findings influence very long-term prognosis. Methods and Results: A total of 102 consecutive patients (75 males, mean age 65 ± 10 years) referred to our center for CRT implantation had previously been included in this prospective observational study. The same patient group was now re-evaluated for death from all causes over a prolonged median follow-up of 10.3 years (interquartile range 9.4–12.5 years). During follow-up, 55 patients died, and 82% of the clinical non-responders (n = 23) and 44% of the responders (n = 79) were deceased. We screened for univariate associations and found QRS width during biventricular (BIV) pacing (p = 0.02), left ventricular (LV) pacing (p < 0.01), Δ LV paced–right ventricular (RV) paced (p = 0.03), age (p = 0.03), New York Heart Association (NYHA) class (p < 0.01), CHA2DS2-Vasc score (p < 0.01), glomerular filtration rate (p < 0.01), coronary artery disease (p < 0.01), non-ischemic cardiomyopathy (NICM) (p = 0.01), arterial hypertension (p < 0.01), NT-proBNP (p < 0.01), and clinical response to CRT (p < 0.01) to be significantly associated with mortality. In the multivariate analysis, NICM, the lower NYHA class, and smaller QRS width during BIV pacing were independent predictors of better outcomes. Conclusion: Our data show that QRS width duration during biventricular pacing, an ECG parameter easily obtainable during LV lead placement, is an independent predictor of mortality in a long-term follow-up. Our data add further evidence that NICM and lower NYHA class are independent predictors for better outcome after CRT implantation.